Automatic Distance Monitoring System of Contact Connections in High Voltage Equipment of Electric Power Lines - M. D. Diachenko; Yu. A. Teslia (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The developed automatic distance monitoring system of contact connections in high voltage equipment is based on technology of sensor circuits. The paper shows application of control methodology for contact connections in accordance with time rate of conductor temperature changes and contact connection and also direct measurement of transient resistance.